2012
DOI: 10.5194/acp-12-371-2012
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of natural and anthropogenic very short-lived species to stratospheric bromine

Abstract: Abstract.We have used a global three-dimensional chemical transport model to quantify the impact of the very short-lived substances (VSLS) CHBr 3 , CH 2 Br 2 , CHBr 2 Cl, CHBrCl 2 , CH 2 BrCl and C 2 H 5 Br on the bromine budget of the stratosphere. Atmospheric observations of these gases allow constraints on surface mixing ratios that, when incorporated into our model, contribute ∼4.9-5.2 parts per trillion (ppt) of inorganic bromine (Br y ) to the stratosphere. Of this total, ∼76 % comes from naturally-emitt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
99
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(117 citation statements)
references
References 25 publications
(49 reference statements)
14
99
4
Order By: Relevance
“…Elevated BrO concentrations are measured within the LS (range 3-9 ppt), and lower BrO concentrations are measured in the TTL (range 0.5-5 ppt), with the smallest BrO concentrations (0.5-1 ppt) occurring near the bottom of the TTL. Overall, this behavior is expected from arguments based on the amount and composition of the brominated organic and inorganic source gases, their lifetimes, atmospheric transport, and photochemistry (e.g., Fueglistaler et al, 2009;Aschmann et al, 2009;Hossaini et al, 2012b;Ashfold et al, 2012;WMO, 2014;Fernandez et al, 2014;Saiz-Lopez and Fernandez, 2016). In particular, for our daytime measurements, it is observed that (a) BrO increases with O 3 and available Br inorg y and thus altitude and (b) the predicted BrO / Br inorg y ratio decreases towards the bottom of the TTL, where (c) HBr and/or Br atoms may become comparable to BrO, but HOBr does not play a major role in the Br inorg y partitioning.…”
Section: Comparisons Of Measured Bro With Previous Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated BrO concentrations are measured within the LS (range 3-9 ppt), and lower BrO concentrations are measured in the TTL (range 0.5-5 ppt), with the smallest BrO concentrations (0.5-1 ppt) occurring near the bottom of the TTL. Overall, this behavior is expected from arguments based on the amount and composition of the brominated organic and inorganic source gases, their lifetimes, atmospheric transport, and photochemistry (e.g., Fueglistaler et al, 2009;Aschmann et al, 2009;Hossaini et al, 2012b;Ashfold et al, 2012;WMO, 2014;Fernandez et al, 2014;Saiz-Lopez and Fernandez, 2016). In particular, for our daytime measurements, it is observed that (a) BrO increases with O 3 and available Br inorg y and thus altitude and (b) the predicted BrO / Br inorg y ratio decreases towards the bottom of the TTL, where (c) HBr and/or Br atoms may become comparable to BrO, but HOBr does not play a major role in the Br inorg y partitioning.…”
Section: Comparisons Of Measured Bro With Previous Studiesmentioning
confidence: 99%
“…In the present context the most important were measurements performed within the TTL (for the definition of TTL, see Fueglistaler et al, 2009) over the Pacific from where most of the stratospheric air is predicted to originate (e.g., Fueglistaler et al, 2009;Aschmann et al, 2009;Hossaini et al, 2012b;Ashfold et al, 2012;WMO, 2014;Orbe et al, 2015). These include the measurements (a) by Schauffler et al (1993Schauffler et al ( , 1998Schauffler et al ( , 1999, who found [VSLS] = 1.3 ppt (contribution 3) at the tropical tropopause over the central Pacific (Hawaii) in 1996, (b) by Laube et al (2008) and Brinckmann et al (2012) Supporting information on brominated VSLS concentrations typical of the boundary layer of the western Pacific came from measurements performed during the TransBrom ship cruise in October 2009 (median 2.23 ppt and range from 1.45-4.14 ppt; Brinckmann et al, 2012) and the VSLS measurements made around Borneo during the SHIVA (Stratospheric Ozone: Halogen Impacts in a Varying Atmosphere) project (median 5.7 ppt and range from 3.9 to 10.7 ppt; Sala et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Being short lived, there are large uncertainties in using atmospheric concentration measurements to estimate their global fluxes and their net contribution to the stratospheric bromine (Warwick et al, 2006;Liang et al, 2010;Pyle et al, 2011;Ordóñez et al, 2012;Ziska et al, 2013;Hossaini et al, 2013). A large range of contributions to stratospheric inorganic bromine of 110 ppt can be found in the literature (Dorf et al, 2008;Salawich et al, 2010;Schofield et al, 2011;Aschmann et al, 2011;Tegtmeier et al, 2012;Stachnik et al, 2013;Hossaini et al, 2012a). The UNEP/WMO ozone assessment of 2011 reports the value as 6(3-8) ppt (Montzka, Reimann et al, 2011).…”
Section: Introductionmentioning
confidence: 98%
“…They may be the dominant source of Br y in the upper troposphere and lowermost stratosphere (Dvortsov et al, 1999;Salawitch et al, 2005). Bromoform (CHBr 3 ) and dibromomethane (CH 2 Br 2 ) have received most attention, and appear to account for the bulk of bromine bound within VSLS (Hossaini et al, 2012). A further organic source of bromine is…”
Section: Introductionmentioning
confidence: 99%